Verify this!

Geometry Level 5

sin x + tan 2 x + sin 3 x + tan 4 x + + sin 2 n 1 x + tan 2 n x > 2 \sin x+\tan^2 x+\sin^3 x+\tan^4 x+\cdots+\sin^{2n-1}x+\tan^{2n}x>\sqrt{2} With n N n\in\mathbb{N^*} and x ( 0 ; π 6 ) x\in \left(0;\frac{\pi}{6}\right) , what can be said about the above inequality.

True for all n n Depends on n n False for all n n

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

P C
Dec 13, 2016

In ( 0 ; π 6 ) \big(0;\frac{\pi}{6}\big) both s i n x sinx and t a n x tanx increase. So now consider the L H S LHS L H S < s i n ( π 6 ) + t a n 2 ( π 6 ) + s i n 3 ( π 6 ) + t a n 4 ( π 6 ) + . . . + s i n 2 n 1 ( π 6 ) + t a n 2 n ( π 6 ) LHS < sin\big(\frac{\pi}{6}\big)+tan^2\big(\frac{\pi}{6}\big)+sin^3\big(\frac{\pi}{6}\big)+tan^4\big(\frac{\pi}{6}\big)+...+sin^{2n-1}\big(\frac{\pi}{6}\big)+tan^{2n}\big(\frac{\pi}{6}\big) The above R H S RHS equals to 1 2 + ( 1 3 ) 2 + . . . + ( 1 2 ) 2 n 1 + ( 1 3 ) 2 n \frac{1}{2}+\bigg(\frac{1}{\sqrt{3}}\bigg)^2+...+\bigg(\frac{1}{2}\bigg)^{2n-1}+\bigg(\frac{1}{\sqrt{3}}\bigg)^{2n} Now we consider these following sum A = 1 2 + ( 1 2 ) 3 + . . . + ( 1 2 ) 2 n 1 A=\frac{1}{2}+\big(\frac{1}{2}\big)^3+...+\big(\frac{1}{2}\big)^{2n-1} and B = ( 1 3 ) 2 + ( 1 3 ) 4 + . . . + ( 1 3 ) 2 n B=\big(\frac{1}{\sqrt{3}}\big)^2+\big(\frac{1}{\sqrt{3}}\big)^4+...+\big(\frac{1}{\sqrt{3}}\big)^{2n} . We see that ( 1 2 ) 2 A = ( 1 2 ) 3 + ( 1 2 ) 5 . . . + ( 1 2 ) 2 n + 1 \bigg(\frac{1}{2}\bigg)^2A=\bigg(\frac{1}{2}\bigg)^3+ \bigg(\frac{1}{2}\bigg)^5...+\bigg(\frac{1}{2}\bigg)^{2n+1} ( 1 3 ) 2 B = ( 1 3 ) 4 + ( 1 3 ) 6 . . . + ( 1 3 ) 2 n + 2 \bigg(\frac{1}{\sqrt{3}}\bigg)^2B=\bigg(\frac{1}{\sqrt{3}}\bigg)^4+\bigg(\frac{1}{\sqrt{3}}\bigg)^6...+\bigg(\frac{1}{\sqrt{3}}\bigg)^{2n+2} Therefore A 1 4 A = 1 2 ( 1 2 ) 2 n + 1 A = 4 3 [ 1 2 ( 1 2 ) 2 n + 1 ] < 4 3 . 1 2 = 2 3 A-\frac{1}{4}A=\frac{1}{2}-\bigg(\frac{1}{2}\bigg)^{2n+1}\Rightarrow A=\frac{4}{3}\bigg[\frac{1}{2}-\bigg(\frac{1}{2}\bigg)^{2n+1}\bigg]<\frac{4}{3}.\frac{1}{2}=\frac{2}{3} B 1 3 B = 1 3 ( 1 3 ) 2 n + 2 B = 3 2 [ 1 3 ( 1 3 ) 2 n + 2 ] < 3 2 . 1 2 = 1 2 B-\frac{1}{3}B=\frac{1}{3}-\bigg(\frac{1}{\sqrt{3}}\bigg)^{2n+2}\Rightarrow B=\frac{3}{2}\bigg[\frac{1}{3}-\bigg(\frac{1}{\sqrt{3}}\bigg)^{2n+2}\bigg]<\frac{3}{2}.\frac{1}{2}=\frac{1}{2} So L H S < A + B < 2 3 + 1 2 = 7 6 < 2 LHS<A+B<\frac{2}{3}+\frac{1}{2}=\frac{7}{6}<\sqrt{2} , the correct choice is "False for all n n ".

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...